Study on the effect of "7" and "I" shaped adhesive tape in fixation of nasogastric tubes (“7”字型和“工”字型胶贴对鼻胃管固定效果的研究) - WANG Fengjuan (王凤娟); CHEN Yuezhi (陈月治) (中西医结合护理)
Objective To investigate the effects of two sticking and fixation methods of nasogastric tubes for elderly patients, and to provide reference for clinical practice. Methods Totally 116 elderly patients requiring placement of nasogastric tube were selected and randomly divided into experimental group and control group, with 58 patients in each group. Based on the nursing maintenance of nasogastric tube, the I-shaped sticking and fixation method was used in the control group, while the 7-shaped method was adopted in the experimental group. The slippage and displacement of nasogastric tube adhesive tape, skin condition, frequency of unplanned replacement and consumption of the two groups were observed and compared. Results No patients in either group reported slippage and displacement of nasogastric tube adhesive tape or skin adverse reactions. There was no significant difference in the frequency of unplanned adhesive tape replacement between the experimental group and the control group (P＞0. 05). The incidence of adhesive tape replacement in the experimental group was higher than that in the control group, but with no significant difference(P＞0. 05) . The consumption of adhesive tape in the experimental group was significantly lower than that in the control group(P＜0. 01). Conclusion There was no significant difference in the effect of two kinds of fixation methods for nasogastric tube in elderly patients. The usage of I-shaped was significantly more than that of 7-shape, which was of great significance for promotion. (目的 比较两种胃管粘贴固定方法对留置鼻胃管老年患者鼻胃管的固定效果, 为临床护士选择鼻胃管固定方式提供参考依据。方法 选择某三甲医院干部保健病房留置鼻胃管的老年患者共116例, 根据随机数表法分为试验组和对照组, 各58例。两组患者均采用相同的鼻胃管护理方案, 试验组采用“7”字形方法固定, 对照组采用“工”字形方法固定。观察比较两组患者鼻胃管胶贴滑脱移位、皮肤情况、非常规更换的频次及耗材量。结果 两组均为发生鼻胃管移位及滑脱, 也未发生鼻胃管胶贴固定部位及周围皮肤的异常情况。两组胶贴非常规更换频次差异无统计学意义(P＞0. 05)。“7”字形胶贴因异常原因(变松、潮湿、卷边或脱落等)而被更换的发生率高于“工”字形, 但差异具无统计学意义(P＞0. 05), “7”字形胶贴耗材量低于“工”字形胶贴(P＜0. 01)。结论 两种形状的鼻胃管胶贴固定方法对留置胃管老年患者的鼻胃管固定效果无差异, “7”字形胶贴容易因为变松而被更换, “工”字型使用量明显多于“7”字形, 两种形状胶贴各有优势。)